Getting into the details: structural effects of economic growth on environmental pollution in Ethiopia - Dagmawe Tenaw (Heliyon, 2021)
Reduced-form approaches are like a ‘black-box’ which do not explicitly display the possible channels (exact forces) through which growth may influence the environment. Accordingly, this study aims to provide some empirical evidence regarding the underlying structural effects of growth on emissions of carbon dioxide (CO2), Methane (CH4), and Nitrous oxide (N2O) in Ethiopia over 1975–2017. Autoregressive Distributed Lag (ARDL) model is employed and the results confirm that the scale effect of growth increases all types of emissions in both the short run and long run. And, the composition effect has a long-run monotonically increasing relationship with CO2 emissions and a non-increasing pattern with CH4 and N2O emissions. On the other hand, a generally decreasing (for CO2 emissions) and an Inverted-U shaped (for CH4 and N2O emissions) technique effects of growth are obtained. This indicates that while growth through its technique effect reduces CO2 even at a lower level of income, the country needs to achieve a higher income level for the technique effect to be effective in reducing CH4 and N2O emissions. Fossil fuel energy appears to be the main driver of environmental pollution. Furthermore, the Toda-Yamamoto Granger causality test indicates a unidirectional causality from the three structural components of growth to all emissions. The findings, generally, suggest that a self-correcting mechanism in the growth process may not automatically reduce environmental pollution. Quite simply, to achieve environmentally sustainable economic growth, the technique effect should be sufficiently strong to offset the scale effect.